Employability Skills dan Pengaruhnya terhadap Penghasilan Lulusan SMK Teknologi Industri - Sumarno Sumarno (Universitas Negeri Yogyakarta, 2008)
This study was aimed at revealing: (1) the effect of the work experience (working period and training period) on employability skills mastery level (technological skills, fundamental skills, personal management skills, and work skills); and (2) the effect of working period, employability skills mastery level, employability skills used, andfrequency of employability skills used on earnings. The subjects of the study were ITHVS graduate workforces of Bandar Lampung Municipality. The datafor study were collected through questionnaires (selfreports). The statistical analysis techniques used were canonical correlation and multiple regression. The results of the study show that: (1) The canonical independent variable (the working period and training period) has a positive impact on technological skills (with canonical loading 0.98), on fundamental skills (0.06), on personal management skills (0.57), on team work skills (0.12); and (2) the earning received by the ITVHS' graduate workers is only affected by their workingperiod (earnings = 698,185 + 23,383 workingperiod)